The Emphasis on Grouping Students to Explore Length and Area of Conservation Tasks Skills in Grade 5 Elementary School - Kodirun, Kodirun; Salam, Mohamad; Misu, La (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
This study investigates how a geometric plane with a similar area can have different circumferences, and how a geometric plane with the same area can have different areas. Classroom learning is TPS, with an emphasis on maximizing group work. Two students of 107 of 5th elementary school graders were selected by convenience sampling to be interviewed. The findings show that group discussions help students develop and improve their individual mathematical abilities; students can determine geometric planes with similar areas but different circumferences and geometric planes with different areas but similar circumferences; and 5th graders  students can conserve length or area of some geometric planes